التفاوت في التراجم الأدبية بين المادة و المكانة: مشاهير يتيمة الدهر للثعالبي أنموذجا - مزوار, نبيل (جامعة الوادي - University of Eloued, 2017)
يلاحظ الدارس لكتاب يتيمة الدهر في محاسن أهل العصر لأبي منصور الثعالبي تفاوتا ظاهرا في مقدار الترجمة بين علم و آخر ، ففي الوقت الذي أسال فيه المؤلف مدادا غزيرا في بعض الترجمات حتى ربت عن مائة وأربعين صفحة ، كان قلمه بالمقابل شحيحا في غيرها ، إذ لم تتجاوز ترجمته لها السطرين ، مع وفرة المادة لتناوله للمعاصرين له ، والأكثر من ذلك أنهم أعلام القرن الرابع الهجري ، و الدليل على ذلك حضور من قصرت تراجمهم في مصادر عاصرته فضلا عن المتأخرة عنه . ويحاول هذا المقال الوقوف عند أهم الطبقات التي خصها الثعالبي بعنايته من الشعراء في ذلك الكتاب النفيس ، ودواعي تمييزه لها، وإطالته فيها ،علاوة عما ذكر من عناصر الترجمة الأدبية The analyst of the book (YATIMATO ADDAHRI FI MAHASSEN AHLI AL ASSR) ''the Era's orphan in the beauties of the people of the epoch'' for Abu Mansour al-Thaalibi observes a clear difference in the amount of biography between one scholar and another. While I asks the author a massive information in some biographies until they had a hundred and forty pages, his pen, in contrast, was scarce in others which did not exceed two lines, in spite of the available material to be addressed to his contemporaries, and more than that, they are the scholars of the fourth century AH, and the evidence of that is the presence of the shortened biographies in the sources of his contemporaries as well as the late ones. This article tries to shed light on the most important classes of poets that Thaalibi singled out with care in that precious book, and of distinction as well as extending of them, in addition to the literary translation elements.
مقال
Keywords: التفاوت ؛ التراجم الأدبية ؛ المادة ؛ المكانة مشاهير يتيمة الدهر؛ الثعالبي أنموذجا